1989
DOI: 10.1016/0304-3959(89)90191-7
|View full text |Cite
|
Sign up to set email alerts
|

Pain development and consumption of analgesics after oral surgery in relation to personality characteristics

Abstract: In the present study a survey has been performed of the pain development and analgesic intake in 100 patients following elective oral surgery of impacted third molars in relation to preoperative assessment of personality characteristics. Our results show that no sex differences existed preoperatively concerning personality characteristics, concerning postoperative pain development or analgesic consumption. Fourteen patients reported no pain at all and 40 patients did not use any analgesics in the postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
2
10
0
4
Order By: Relevance
“…Pain measures included VAS at one and three days postoperatively and analgesic use; while psychological measures included STAI, VAS (anxiety), General Health 17 found that personality characteristics are unrelated to postoperative pain following a study on 100 patients undergoing surgical removal of impacted third molars. Faucett et al 18 conducted a study to examine differences in severity of postoperative pain among 543 patients from four ethnic groups (Asian, Black American, European and Latino).…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Pain measures included VAS at one and three days postoperatively and analgesic use; while psychological measures included STAI, VAS (anxiety), General Health 17 found that personality characteristics are unrelated to postoperative pain following a study on 100 patients undergoing surgical removal of impacted third molars. Faucett et al 18 conducted a study to examine differences in severity of postoperative pain among 543 patients from four ethnic groups (Asian, Black American, European and Latino).…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
“…[16][17][18][19] Of these, three examined the predictive capacity of psychosocial factors on postoperative pain and recovery following surgical removal of third molars. One study found psychological factors, including postoperative anxiety, to predict postoperative pain.…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
See 3 more Smart Citations